2020
DOI: 10.1002/ana.25964
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Cessation of Dabigatran Causes a Paradoxical Prothrombotic State

Abstract: Objective It is unclear if stopping treatment with dabigatran, a new oral anticoagulant (NOAC), induces a paradoxical rebound prothrombotic state. We investigated if short‐term (1–3 days) dabigatran cessation is associated with a higher thrombus volume than expected from a simple reversal of the anticoagulant effect. Methods Ten‐week‐old C57Bl/6 mice (n = 338) received one of the following oral treatments: phosphate‐buffered saline (PBS), dabigatran for 7 days with or without 1 to 4 day cessation, and aspirin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Antiplatelet therapy is known to preferentially reduce the incidence of LAA stroke rather than CE or SVO stroke. 45 Yet, previous research has shown that platelet activation plays important roles in CE as well as in LAA stroke, 46,47 which may accord with results on aspirin-related lower thrombus burden (as was also demonstrated in our recent preclinical study on carotid artery thrombosis 48 ) and less frequent early neurological deterioration in CE stroke. On the other hand, platelet activation appears to be less important in SVO stroke, which mainly results from chronic hypertension-mediated lipohyalinosis of small arterioles.…”
Section: Discussionsupporting
confidence: 80%
“…Antiplatelet therapy is known to preferentially reduce the incidence of LAA stroke rather than CE or SVO stroke. 45 Yet, previous research has shown that platelet activation plays important roles in CE as well as in LAA stroke, 46,47 which may accord with results on aspirin-related lower thrombus burden (as was also demonstrated in our recent preclinical study on carotid artery thrombosis 48 ) and less frequent early neurological deterioration in CE stroke. On the other hand, platelet activation appears to be less important in SVO stroke, which mainly results from chronic hypertension-mediated lipohyalinosis of small arterioles.…”
Section: Discussionsupporting
confidence: 80%
“…Mice were anesthetized with an induction chamber using 2 ~ 2.5% isoflurane mixed with 30% oxygen (1.5 L/min), and in situ carotid thrombus was formed (n = 72) by an experienced researcher (J. Kim), as has been previously reported 37,38 , by applying a strip of 1 × 1 mm 2 filter paper (grade 42; Whatman, Oxon, UK) soaked in 4 μL 10% FeCl 3 to the left common carotid artery (CCA) for 10 min after exposing the vessel by a midline neck incision and dissection of the perivascular tissue. We previously demonstrated that similar-sized carotid thrombi can be consistently generated at the hands of a skillful researcher 39 . In sham-operated animals (n = 79), the left CCA was exposed to saline-soaked filter paper for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…This platelet inhibitory effect appears to be dose-dependent [ 166 ]. Interestingly, cessation of dabigatran may induce a state of platelet activation [ 167 ]. Those antiplatelet effects have also been proposed for the factor Xa inhibitors [ 168 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%